2002
DOI: 10.1097/00006123-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oxygenation and Energy Metabolism: Part I???Biological Function and Pathophysiology

Abstract: CONTINUOUS OXYGEN DELIVERY and CO(2) clearance are paramount in the maintenance of normal brain function and tissue integrity. Under normal conditions, aerobic metabolism is the major source of energy in the brain, but this system may be compromised by the interruption of substrate delivery and disturbances in cerebral metabolism. These disruptions are major factors contributing to ischemic and hypoxic brain damage resulting from traumatic brain injury, stroke, and subarachnoid hemorrhage. There is evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 104 publications
2
128
0
9
Order By: Relevance
“…Mechanoporation, ischemia, and energy failure at the level of mitochondria are some of the causes of ionic and neurochemical cascades contributing to cytotoxic brain edema and intracranial hypertension resistant to maximal medical management. 7,8,[12][13][14]17,23,30,58,71,72,74,91,92,99,115,118,124 Adherence to published prehospital, intensive care, and surgical guidelines for the management of severe head injury has lessened the burden of hypotension or hypoxia and has mitigated deleterious effects of increased ICP due to brain swelling; 4,6,18,22,43,76,79 nevertheless, straightforward correction of pathophysiological pathways and neurochemical cascades has not been easy. Translational research on severe head injury has revealed no easy pharmaceutical therapy for severe head injury and cerebral swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanoporation, ischemia, and energy failure at the level of mitochondria are some of the causes of ionic and neurochemical cascades contributing to cytotoxic brain edema and intracranial hypertension resistant to maximal medical management. 7,8,[12][13][14]17,23,30,58,71,72,74,91,92,99,115,118,124 Adherence to published prehospital, intensive care, and surgical guidelines for the management of severe head injury has lessened the burden of hypotension or hypoxia and has mitigated deleterious effects of increased ICP due to brain swelling; 4,6,18,22,43,76,79 nevertheless, straightforward correction of pathophysiological pathways and neurochemical cascades has not been easy. Translational research on severe head injury has revealed no easy pharmaceutical therapy for severe head injury and cerebral swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue hypoxia-induced by brain insults plays a critical role in the primary and secondary events leading to cell death after cerebral ischemia (Zauner et al, 2002). Therefore, improving brain tissue oxygenation is a logical and important strategy of stroke treatment to delay the transition of ischemia to infarction (“buying time”).…”
Section: Changes Of Oxygen Tension In Brain Tissues During Different mentioning
confidence: 99%
“…Hypoxia modifies the activity of the cytochrome chain responsible for mitochondrial oxidative phosphorylation, resulting in a decrease in ATP synthesis and increased ROS [9] at the same time as a decrease in the activity of the cellular antioxidant system [5], [10], which may lead to oxidative stress. The brain is particularly vulnerable to the effects of ROS for several reasons: (a) it has a low catalase and glutathione peroxidase activity [11], (b) it is rich in lipids with unsaturated fatty acids that can react with ROS and generate peroxyl radicals that oxidize the lipid membrane [12], (c) it has a high metabolic activity and high oxygen consumption [13].…”
Section: Introductionmentioning
confidence: 99%